Longitudinal study of accelerated long-term forgetting in children with genetic generalized epilepsy: Evidence of ongoing deficits. (January 2019) - Grayson-Collins, Jasmin; Gascoigne, Michael B.; Barton, Belinda; Webster, Richard; Gill, Deepak; Lah, Suncica
Abstract: Accelerated long-term forgetting (ALF) is a recently described memory disorder characterised by adequate recall after short, but not long delays. Currently, the prevailing conceptualisation of ALF is of a seizure related phenomenon. The main aim of this study was to assess whether ALF subsides as epilepsy severity and seizures abate in children with genetic generalized epilepsy (GGE). Eighteen children with GGE were compared over time to 29 healthy controls on a range of cognitive measures. The primary outcome was a modified version of the California Verbal Learning Test for Children with a long delay (seven day) recall component. At approximately two years follow up, ALF was apparent, although epilepsy severity subsided and seizures resolved in many children. This result contrasts with the dominant conceptualisation of ALF being a seizure related phenomenon. Moreover, at follow-up, worse recall at the long delay was related to greater epilepsy severity at baseline and earlier age of seizure onset, but not to being seizure free at follow-up. While at follow-up worse recall at the long delay related to the worse baseline recall at the long delay, this recall did not relate to scores obtained on standardised memory tests at baseline. Our study suggests that ALF may not be seizure related and identifies factors associated with risk of ALF in children with GGE.